THE CORRELATION BETWEEN LEPTIN LEVELS WHEN PARTUS AND ESTROGEN LEVELS ESTRUS POST-PARTUS ON BALI CATTLE - Suparman, I Putu; Trilaksana, I Gusti Ngurah Bagus; Laksmi, Desak Nyoman Dewi Indira (Buletin Veteriner Udayana, 2022)
Leptin is one of metabolic product that regulates hypothalamus pituitary ovaries. This study aims to determine the relationship of leptin levels during parturition with estrogen levels estrus post-partus in bali cattle. The data source of this research is bali cattle during parturition where the main blood sample is taken less than 24 hours after parturition. Continued sampling of cow's blood when showing symptoms of estrus postpartum. Determination of leptin and estrogen levels was carried out using the Direct Elisa, Double Antibody Sandwich method. Data were analyzed descriptively with the Correlation and Regression statistical tests. The results showed that the average level of leptin hormone at parturition ( ± SD) was 2.60 + 0.47 ng/ml and the average level of post-partus leptin estrus hormone ( ± SD) was 5.42 + 0.47 ng/ml. While the average levels of the hormone estrogen estrus post-partus ( ± SD) is 105.51 + 19.72 pg/ml. This shows an increase in the level of the hormone leptin from parturition to estrus post-partus which has an impact on increasing estrogen levels. By using a linear regression test it was found that leptin hormone levels had a positive effect on estrogen hormone levels. From the results of the study it can be concluded that there is a close relationship between leptin levels during parturition with estrogen levels during estrus post-partus.